Illegal Mining and Penal Law Enforcement in Lampung, Indonesia: Study for Environmental Justice and Governance - Dzaky Muhammad Haris (Corruptio, 2025)
This article critically examines the effectiveness of penal law enforcement against illegal mining in Lampung Province, Indonesia, through a normative–empirical approach. Lampung is selected as the research locus because its illegal mining dynamics differ fundamentally from those of Indonesia’s major mining regions such as Kalimantan, Sulawesi, and Papua. In contrast to regions where mining is embedded in formal development frameworks and dominated by large-scale corporate actors, illegal mining in Lampung is predominantly informal, small-scale, and community-based, yet generates significant environmental degradation. This distinctive configuration reveals regulatory challenges that are insufficiently addressed by Indonesia’s nationally uniform mining and penal policies. Applying criminal policy framework formulation, application, and execution, this study identifies structural weaknesses that manifest acutely in Lampung. The formulation stage produces legal uncertainty through excessive centralization authority, decriminalization of abusive official conduct, and regulatory norms that disproportionately criminalize local communities. These problems are intensified by limited local regulatory discretion, creating a disjunction between centralized legal norms and local socio-ecological realities. The application law enforcement exhibits a persistent gap between actual and recorded illegal mining activities, compounded by fragmented inter-agency coordination. The execution of judicial sanctions remain largely symbolic due to ambiguous legal mechanisms governing fines, asset forfeiture, and environmental restoration. The article advances the novel argument that Indonesia’s penal response to illegal mining suffers not merely from weak enforcement, but from a structural mismatch between centralized criminal regulation and region-specific mining practices. This study contributes to socio-legal and environmental law scholarship by demonstrating the limitations of uniform penal frameworks and emphasizing the need for region-sensitive regulatory and enforcement models oriented toward substantive justice and ecological protection.